A Closer Look at the Behavior of Uncertainty and Disagreement: Micro Evidence from the Euro Area. Issue 1 (8th September 2020) - RICH, ROBERT; TRACY, JOSEPH
Abstract: This paper examines point and density forecasts of real GDP growth, inflation, and unemployment from the European Central Bank's Survey of Professional Forecasters. We analyze individual uncertainty measures as well as introduce individual point‐ and density‐based disagreement measures. The analysis indicates forecasters' uncertainty and disagreement display substantial heterogeneity and persistence, with the latter feature challenging a key prediction of expectations models emphasizing information frictions. We also find that uncertainty is characterized by prominent respondent effects and disagreement by prominent time effects, suggesting these divergent properties underlie the well‐documented weak uncertainty–disagreement linkage. Taken together, our results provide a basis for further development of expectations models.